Accurate crystal structures and chemical properties from NoSpherA2. Issue 5 (15th December 2020) - Kleemiss, Florian; Dolomanov, Oleg V.; Bodensteiner, Michael; Peyerimhoff, Norbert; Midgley, Laura; Bourhis, Luc J.; Genoni, Alessandro; Malaspina, Lorraine A.; Jayatilaka, Dylan; Spencer, John L.; White, Fraser; Grundkötter-Stock, Bernhard; et al.
Abstract : NoSpherA2 brings quantum crystallography to routine structure determination and to the analysis of chemical properties for any class of materials. Abstract : The relationship between the structure and the properties of a drug or material is a key concept of chemistry. Knowledge of the three-dimensional structure is considered to be of such importance that almost every report of a new chemical compound is accompanied by an X-ray crystal structure – at least since the 1970s when diffraction equipment became widely available. Crystallographic software of that time was restricted to very limited computing power, and therefore drastic simplifications had to be made. It is these simplifications that make the determination of the correct structure, especially when it comes to hydrogen atoms, virtually impossible. We have devised a robust and fast system where modern chemical structure models replace the old assumptions, leading to correct structures from the model refinement against standard in-house diffraction data using no more than widely available software and desktop computing power. We call this system NoSpherA2 (Non-Spherical Atoms in Olex2). We explain the theoretical background of this technique and demonstrate the far-reaching effects that the improved structure quality that is now routinely available can have on the interpretation of chemical problems exemplified by five selected examples.